Nb12+—niobespherene: a full-metal hollow-cage cluster with superatomic stability and resistance to CO attack. Issue 3 (22nd September 2022) - Huang, Benben; Zhang, Hanyu; Gan, Wen; Yang, Mengzhou; Luo, Zhixun; Yao, Jiannian
ABSTRACT: Why one chemical is more stable than another is not always easy to understand. A unified answer for metal clusters has led to the establishment of the superatom concept, which rationalizes the delocalization of electrons; however, cluster stability based on superatom theory has not been confirmed unambiguously for any metal other than the s- and p-blocks of the periodic table of elements. Here, we have prepared pure niobium clusters and observed their reactions with CO under sufficient gas collision conditions. We find prominent inertness of Nb12 +, which survives CO attack. Comprehensive theoretical calculation results reveal that the inertness of Nb12 + is associated with its cage structure and well-organized superatomic orbitals, giving rise to energetic superiority among the studied clusters. It is revealed that not only the 5s but also the 4d electrons of Nb delocalize in the cluster and significantly contribute to the superatomic state, resulting in reasonable cage aromaticity. This hollow-cage cluster, which we have called a 'niobespherene', provides a clue with regard to designing new materials of all-metal aromaticity and Nb-involved catalysts free of CO poisoning. Abstract : The reactions of niobium clusters with carbon monoxide find a CO-tolerent full-metal cluster Nb12 + (named niobespherene) which exhibits prominent stability and cage aromaticity and is one of ideal carriers for new catalysts.